The Influence of Tourist Attractions, Artificial Intelligence (Ai)-Based Digital Marketing Strategies, and Financial Management Accountability on the Success of Tourism Village Development: a Study Of Tourism Village Managers in Denpasar City - Ni Putu Ina Trhisnawati Weca; Ni Made Devi Ratnasari; Ketut Winda Pratiwi (PT Keberlanjutan Strategis Indonesia, 2026)
Abstract:This study examines the effects of tourism attractions, Artificial Intelligence (AI)-based digital marketing strategies, and financial management accountability on tourism village development success in Denpasar City. It addresses empirical gaps concerning the effectiveness of AI-enabled marketing in tourism villages and the inconsistent evidence regarding the role of financial accountability. An explanatory quantitative approach with a cross-sectional survey design was applied to 70 tourism village managers. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that all three independent variables have positive and statistically significant effects. AI-based digital marketing strategies are the most dominant determinant (β = 0.391; p < 0.001), followed by financial management accountability (β = 0.318; p < 0.001) and tourism attractions (β = 0.230; p = 0.029). The model explains 49.8% of the variance in tourism village development success. These findings indicate that tourism village development in Denpasar City is primarily driven by AI-based digital marketing capabilities, supported by competitive tourism attractions and accountable financial governance. Tourism village managers should therefore integrate digital innovation, participatory governance, and robust financial management systems to promote sustainable economic, social, and institutional development.